Drew Gardner: capstone - Gardner, Drew, artist (Colorado State University. Libraries, 2026)
The artist's statement: For as long as I can remember I used art as my second language. A language that allowed me to communicate when my words had failed, which they often did. Through video, watercolor, even poetry I seek to connect and speak with my viewer, letting them peer into my mind even for just a minute. My practice is heavily inspired by grief, nostalgia, and the idea of identity. These experiences, while personal, are universal as well. Everyone on the planet has had a childhood, a sense of self, and something they've lost. None of us are alone in these experiences, no matter how it might feel. I try my hardest to explore these themes through a multitude of mediums. Whether that be sculpture, site specific work, or drawing. I'm always working to create my vision in whatever form that may take. At the moment video has been my primary medium as I navigate loss, particularly through the voicemails that litter my inbox.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art